2011
DOI: 10.1016/b978-0-12-385506-0.00010-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Serotonergic System in Alcohol Dependence

Abstract: Alcohol dependence remains among the most common substance abuse problems worldwide, and compulsive alcohol consumption is a significant public health concern. Alcohol is an addictive drug that alters brain function through interactions with multiple neurotransmitter systems. These neurotransmitter systems mediate the reinforcing effects of alcohol. Specifically, the serotonergic system is important in mediating alcohol reward, preference, dependence, and craving. In this review chapter, we first discuss the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 294 publications
(352 reference statements)
4
92
0
3
Order By: Relevance
“…The use of baclofen is controversial, however, because of potent sedative and muscle relaxant actions that are additive with alcohol and additional interactions with other drugs of abuse. Drugs targeting the opioid, DA, and 5-HT neurotransmitter systems have also been proposed as novel alcoholism therapies (15)(16)(17), but only one drug (naltrexone) is Food and Drug Administration approved. Clearly,…”
Section: Rgs6mentioning
confidence: 99%
“…The use of baclofen is controversial, however, because of potent sedative and muscle relaxant actions that are additive with alcohol and additional interactions with other drugs of abuse. Drugs targeting the opioid, DA, and 5-HT neurotransmitter systems have also been proposed as novel alcoholism therapies (15)(16)(17), but only one drug (naltrexone) is Food and Drug Administration approved. Clearly,…”
Section: Rgs6mentioning
confidence: 99%
“…The serotonergic system has been shown to be important in mediating alcohol reward, preference, dependence, and craving 25 . Studies concerning the association of alcohol dependence with serotonin polymorphisms generally have focused on the serotonin transporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of neurotransmitters in the mesolimbic pathway (e.g., dopamine (DA), GABA, opioids, and serotonin (5-HT)) interact with GPCRs, G protein-dependent signaling may offer a therapeutic target in the treatment of alcohol abuse. With this in mind, multiple drugs targeting these neurotransmitter receptors have been recommended for the treatment of alcoholism (40)(41)(42). One such drug, baclofen, a GABA B R agonist, has been approved in Europe as a treatment for alcohol withdrawal symptoms and cravings (43)(44)(45).…”
Section: Alcohol Use Disordersmentioning
confidence: 99%
“…In addition, there was also evidence to suggest that RGS6 was capable of regulating the signaling of other GPCRs, such as 5-HT 1A Rs and μ-opioid receptors (22,46), which had already been identified as potential therapeutic targets in the treatment of alcoholism (40,42). Both immunohistochemical and western blot studies in wild type (RGS6+/+) mice subsequently demonstrated that RGS6 protein expression was upregulated in the ventral tegmental area (VTA) of the mesolimbic system following prolonged alcohol exposure.…”
Section: Alcohol Use Disordersmentioning
confidence: 99%